Low-fat, low-cholesterol cookbook : delicious recipes to help lower your cholesterol. - American Heart Association (New York : Clarkson Potter, 2008)
Contains heart-healthy recipes for appetizers and snacks, soups, salads and dressings, seafood, poultry, meats, vegetarian entrees, vegetables and side dishes, breads and breakfast dishes, beverages, and desserts, each with a nutritional analysis. Includes information on how to control cholesterol levels, and strategies for reducing the risk of heart disease and stroke.
Includes index.
Running title: American Heart Association low-fat, low-cholesterol cookbook.
Adult
Keywords: Low-cholesterol diet -- Recipes; Low-fat diet -- Recipes; Cooking; Low-cholesterol diet; Low-fat diet